Pengembangan E-Modul Berbasis STEM-PjBL pada Materi Laju Reaksi untuk Meningkatkan Hasil Belajar - Sari, Mayang; Amdayani, Susilawati (Pedagogi: Jurnal Ilmu Pendidikan, 2025)
The development of STEM-PjBL based E-Modules reaction rate material is an innovation that combines 21st century approach and learning model. The purpose of this study to analyze the needs of students, feasibility level, practicality level, effectiveness and student responses to STEM-PjBL based E-Modules. The method used is Research and Development with the 4D (Define, Design, Develop, Disseminate) development model. The research sample were students of class XI-1 SMAN 1 Kisaran. Tests, questionnaires and interviews were used to analyze the data. The results showed that 69.7% of the students had difficulty in understanding the response rate and 87.9% needed interactive project-based teaching materials. The e-modules feasibility test showed an average kappa moment of 0.84 (very high), practicality test an average kappa moment of 0.99 (very high), the effectiveness obtained N-gain of 0.78 (high), and the student response test to the STEM-PjBL based E-Modules with average kappa moment of 0.92 (very high).